2022
DOI: 10.1038/s41591-022-01956-3
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of human neural progenitor cells secreting GDNF into the spinal cord of patients with ALS: a phase 1/2a trial

Abstract: Amyotrophic lateral sclerosis (ALS) involves progressive motor neuron loss, leading to paralysis and death typically within 3–5 years of diagnosis. Dysfunctional astrocytes may contribute to disease and glial cell line-derived neurotrophic factor (GDNF) can be protective. Here we show that human neural progenitor cells transduced with GDNF (CNS10-NPC-GDNF) differentiated to astrocytes protected spinal motor neurons and were safe in animal models. CNS10-NPC-GDNF were transplanted unilaterally into the lumbar sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 58 publications
0
54
0
1
Order By: Relevance
“…These questions include (1) how is VEGF-A secretion controlled and how dependent is it on cell state; (2) how are cells facilitating the build-up and release of different amounts of VEGF-A secreted protein outside of gene regulation and (3) why would the uncoupling of VEGF-A secretion and transcript levels be beneficial for ultimate biological function compared to direct control of secretion via the regulation of VEGFA steady state transcript levels. From a biotechnology perspective, our results suggest that approaches to drive secretion to modulate engineered cell therapy function 47 should not rely alone on introducing copies to increase the transcript level of the target gene, but rather could benefit from a holistic engineering of the pathways involved in driving secretion, e.g. modulating the VRS in MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…These questions include (1) how is VEGF-A secretion controlled and how dependent is it on cell state; (2) how are cells facilitating the build-up and release of different amounts of VEGF-A secreted protein outside of gene regulation and (3) why would the uncoupling of VEGF-A secretion and transcript levels be beneficial for ultimate biological function compared to direct control of secretion via the regulation of VEGFA steady state transcript levels. From a biotechnology perspective, our results suggest that approaches to drive secretion to modulate engineered cell therapy function 47 should not rely alone on introducing copies to increase the transcript level of the target gene, but rather could benefit from a holistic engineering of the pathways involved in driving secretion, e.g. modulating the VRS in MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple phase I/II clinical trials have suggested that all subjects tolerated NSC spinal cord implantation procedures and have shown no serious adverse events including cord damage, syrinx, or tumor formation over 2 years post‐grafting. 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 NSC transplantation seems to improve the clinical states of ALS patients; however, no significant difference was detected when looking at slopes of disease progression since most aforementioned clinical trials were neither designed nor powered to measure treatment efficacy. 48 In a case series study, NSC transplantation enhanced dopaminergic activity that could correlate with improved motor function in patients with PD, another neurodegenerative disease.…”
Section: Nscs: Multipotent Stem Cells Within the Cnsmentioning
confidence: 99%
“…Clinical trials are ongoing to prove the efficacy of transplanted PSC-derived astrocytes to boost neuronal survival and slow disease progression. For instance, a phase 1/2a trial in a small cohort of ALS patients (NCT02943850) has shown that a single injection of human NPCs engineered to produce glial cell line-derived neurotrophic factor (GDNF) into the spinal cord is safe, and viable grafts differentiated into astrocytes that may be neuroprotective through increased GDNF production ( Baloh et al, 2022 ).…”
Section: Glial Cellsmentioning
confidence: 99%
“…1–8 Krencik and Zhang, 2011 ; Shaltouki et al, 2013 ; Tcw et al, 2017 ; Canals et al, 2018 ; Li et al, 2018 ; Tchieu et al, 2019 ; Barbar et al, 2020 ; transpl. 9–11 Lepore et al, 2008 ; Song et al, 2017 ; Baloh et al, 2022 . Oligodendrocytes: diff.…”
Section: Introductionunclassified